2021
DOI: 10.1111/bjh.17301
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation sequencing improves BCR‐ABL1 mutation detection in Philadelphia chromosome‐positive acute lymphoblastic leukaemia

Abstract: BCR-ABL1 kinase domain mutation testing in tyrosine kinase inhibitor (TKI)-resistant Philadelphia chromosome-positive (Ph+) acute lymphoblastic leukaemia (ALL) patients is routinely performed by Sanger sequencing (SS). Recently, next-generation sequencing (NGS)-based approaches have been developed that afford greater sensitivity and straightforward discrimination between compound and polyclonal mutations. We performed a study to compare the results of SS and NGS in a consecutive cohort of 171 Ph+ ALL patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
4
6
0
1
Order By: Relevance
“…We also studied the impact of KD BCR::ABL1 mutations before starting the treatment. In our cohort, 2 out of 50 newly-diagnosed B-ALL patients showed mutations, in agreement with a recent study by Soverini et al 11 , who found 3 mutated patients out of 44 patients. This frequency increased when other more sensitive methods have been used 21 , 22 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also studied the impact of KD BCR::ABL1 mutations before starting the treatment. In our cohort, 2 out of 50 newly-diagnosed B-ALL patients showed mutations, in agreement with a recent study by Soverini et al 11 , who found 3 mutated patients out of 44 patients. This frequency increased when other more sensitive methods have been used 21 , 22 .…”
Section: Discussionsupporting
confidence: 93%
“…2 D). Most of the mutations observed were in failure and relapse stages for CML and B-ALL patients, respectively, as previously reported 11 , 19 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…2D). Most of the mutations observed were in failure and relapse stages for CML and B-ALL patients, respectively, as previously reported 11,19 .…”
Section: Discussionsupporting
confidence: 81%
“…Ultra-deep sequencing (UDS) by NGS can be used to track the mutation status along TKI treatment due to its high sensitivity. It can be used to discern between compound mutations or the presence of different subclones in case of multiple mutation ndings 11,12 . Other techniques with similar sensitivity have served to con rm mutations in BCR-ABL1 such as digital PCR (dPCR) and allelespeci c oligonucleotides-PCR (ASO-PCR) 13,14 .…”
Section: Introductionmentioning
confidence: 99%